Characterization and Test of Endophytic Bacterial Isolates to Control Leaf Blight on Acacia Seeds (Acacia crassicarpa) - BR SIAGIAN, ROMAYANJU; Puspita, Fifi; Ali, Muhammad; Alhusaeri, Bayo (Jurnal Online Pertanian Tropik, 2022)
ABSTRACT Acacia is a type of plant that recommended for development of industrial forest plantations (HTI) especially pulp and paper. According to Central Statistics Agency (2020), area of ​​​​acacia HTI in Riau Province 2019 was 2,335,450 ha with a log output of 31,509,228m3 and total pulp export of 2,952.4 million US dollars. The need for paper pulp has increased every year. Problems in acacia nursery area is presence of disease caused by Xanthomonas sp. Bacterial leaf blight causes significant losses in procurement of acacia seedlings, so we need an alternative control with environmentally friendly and sustainable by utilizing potential of biological agents in controlling leaf blight. This aimed to study potential of endophytic bacterial isolates against bacterial pathogen Xanthomonas sp. by adopting a Completely Randomized Design (CRD). The results showed that there were 9 isolates of endophytic bacteria that had inhibitory power against Xanthomonas sp., bacterial isolates in hypersensitivity test did not show symptoms of necrosis in tobacco leaves, results of physiological and biochemical tests on levan test and VP test showed differences in reaction results on tested endophytic bacteria isolates and it was found isolate of endophytic bacteria B8 was effective as an antagonist agent in controlling disease. Keywords: acacia; characterization; endophytic bacteria; in vitro; in vivo; Xanthomonas sp.